On revisiting vital signs IoT sensors for COVID-19 and long COVID-19 monitoring: a condensed updated review and future directions (Journal of Ideas in Health, 2021)
Background: Although the world has been facing the COVID-19 pandemic for over a year, we understand that there are still some challenges in using Internet of Things (IoT) devices as allies in this fight. Among the main difficulties, we can mention the selection of appropriate devices and the correct measurement and subsequent analysis of previously obtained vital signs. Methods: In this context, we present a condensed compilation of IoT devices to monitor the vital signs often used to monitor COVID-19. We focus on easy-to-use devices currently available on the market to the general user. Also, the presented analysis is helpful for long COVID-19 monitoring, which is particularly useful to governments and hospitals to analyze eventual sequels on those citizens who tested positive beforehand.Results: The review resulted in 148 heterogeneous devices offering different capabilities. Our first contribution resides in detailing several aspects of each IoT device, indicating which are the most suitable for particular use-case situations. Moreover, our article introduces some challenges and insights into assembling a smart city composed of IoT devices.Conclusion: Here, technological trends such as Serverless computing, homomorphic cryptography, Federated Learning, Elixir programming language, Web Assembly, and vertical elasticity are discussed towards enabling vital sign-driven data capturing and processing. Although there are several IoT devices for health monitoring, there is still work to standardize data formats and APIs for data extraction.
Keywords: COVID-19, Vital Signs, Internet of Things, Smart City, Wearables, Smartwatch, Brazil